2022
DOI: 10.1186/s12931-022-01937-7
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline ameliorates silica-induced pulmonary inflammation and fibrosis via inhibition of caspase-1

Abstract: Background Inhalation of dust containing silica particles is associated with severe pulmonary inflammation and lung injury leading to chronic silicosis including fibrotic remodeling of the lung. Silicosis represents a major global health problem causing more than 45.000 deaths per year. The inflammasome-caspase-1 pathway contributes to the development of silica-induced inflammation and fibrosis via IL-1β and IL-18 production. Recent studies indicate that tetracycline can be used to treat inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recently, it is shown that GSDMD-dependent pyroptosis is triggered in silica-treated AMs by activating the TLR4/NLRP3/caspase-1/GSDMD pathway, which results in aggravated pulmonary inflammation and diffuses silicon nodules [ 66 , 83 ]. Blocking pyroptosis of macrophages by inhibiting the NLRP3 inflammasome or caspase-1 reduces silica-mediated pulmonary inflammation and fibrosis [ 50 , 83 ]. Meanwhile, silica induces the generation of ROS, which is important in the activation of the NLRP3/caspase-1 signaling pathway to accelerate pyroptosis in AMs [ 83 ].…”
Section: Pyroptosis and Inflammation-related Respiratory Diseasesmentioning
confidence: 99%
“…Recently, it is shown that GSDMD-dependent pyroptosis is triggered in silica-treated AMs by activating the TLR4/NLRP3/caspase-1/GSDMD pathway, which results in aggravated pulmonary inflammation and diffuses silicon nodules [ 66 , 83 ]. Blocking pyroptosis of macrophages by inhibiting the NLRP3 inflammasome or caspase-1 reduces silica-mediated pulmonary inflammation and fibrosis [ 50 , 83 ]. Meanwhile, silica induces the generation of ROS, which is important in the activation of the NLRP3/caspase-1 signaling pathway to accelerate pyroptosis in AMs [ 83 ].…”
Section: Pyroptosis and Inflammation-related Respiratory Diseasesmentioning
confidence: 99%
“…Caspase-1 (CASP1) is a major effector protease of pyroptosis. Experimental studies have reported that the inflammasome-caspase-1 pathway contributes to the development of inflammation and fibrosis in the liver and lungs via bioactive IL-1b and IL-18 production (38,39). NOD2 (nucleotide oligomerization domain 2) plays an important role in the host response to bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines play a crucial role in the activation and proliferation of fibroblasts involved in the fibrotic processes seen in silicotic tissues. Research shows that silica exposure increases proliferative responses and cytokine secretion in peripheral blood mononuclear cells (PBMCs) from silicosis patients, indicating a specific modulation of the immune response compared to healthy controls [ 34 ]. This heightened response can lead to increased fibroblast activity and fibrosis, illustrating a direct link between immune cell stimulation by silica and fibroblast-mediated tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%